The Impact Of Post-traumatic Stress Among The Physically Affected In The Battlefield During The17th Of February, 2011 Libyan Revolution On Their Psychological Adjustment. - Fariha Elfaydi,; Ibrahim Mikail; R.A.H Kirembwe (AENSI Publishing, 2024)
Non-Indexed Publication